Solvent‐Dependent Growth of Rigid Styrylstilbene Dicarboxylic Acid Microcrystals as Bent Waveguides and Microlasers. Issue 4 (1st March 2023) - Venkatakrishnarao, Dasari; Hasebe, Shunya; Egawa, Yasunobu; Tapar, Jinal; Paniagua-Domínguez, Ramón; Lau, Chit Siong; Yamagishi, Hiroshi; Tsuji, Hayato; Yamamoto, Yohei
Abstract : Organic single‐crystalline structures can effectively generate and confine photons, which can be potential building blocks for the optical circuits. While designing of organic molecules can tune the photoluminescence (PL) property, it is challenging to achieve efficient laser emission and light resonance in different forms of molecular aggregates. Herein, a dicarboxylated carbon‐bridged oligophenylenevinylene (COPV2‐(COOH)2 ) is newly synthesized. The THF/water solution of COPV2‐(COOH)2 exhibits green‐color PL with quantum yield >0.90 over the range of THF/water = 100/0–40/60. COPV2‐(COOH)2 forms either bent microrods (MR) or microsheets (MS) depending on the crystallization solvents. Significantly, PL resonance and lasing are only observed in MS, indicating that MS has better light confinement property than MR. MS features Q‐factor as high as 1.8 × 10 3 with the lasing threshold of 222 μJ cm −2 . Finite‐difference time‐domain (FDTD)‐simulated electric field distributions in MR and MS validate experimental observations. Abstract : A dicarboxylated carbon‐bridged oligophenylenevinylene (COPV2‐(COOH)2 ), soluble in aqueous solvents with photoluminescence (PL) quantum efficiencies of over 90%, forms either bent microrods (MR) or microsheets (MS) depending on the crystallization solvents. Significantly, PL resonance and lasing are only observed in MS, indicating that MS has better light confinement property than MR.